Measuring Consumers’ Attitude towards Food Labeling: A Study of Interest, Knowledge, Lifestyle, and Contextual View Point - Rahman, Md. Ferdush (Asian Business Review, 2025)
The purpose of food labels is to provide consumers with information that may influence their purchasing decisions. For example, consumers may want to know the ingredients, manufacturing and expiration dates, price, storage requirements, nutritional information, etc. Accurate labeling is essential for informing consumers about the nature and characteristics of the food product and for influencing their purchase decisions. The study was conducted in Rangpur district, Bangladesh, in 2024 to determine how consumer interest, knowledge, lifestyle, and contextual factors affect consumer attitudes toward food labeling in purchase decisions. A total of 300 respondents were interviewed. Both primary and secondary data were used for the study. The questionnaire was developed using a five-point Likert scale. SEM-PLS software was used for data analysis. The SEM results indicated that consumer Knowledge, lifestyle, and Contextual factors were significantly and positively associated with food labeling.